Shadow Economy and Financial Reporting in the Gig Economy Era: A Case Study of Digital Freelance Workers - Ummy Kalsum; Naswan Hadili (Oikonomia : Journal of Management Economics and Accounting, 2025)
The transformation of the digital economy has given rise to a new work model called the gig economy, where digital freelancers operate independently outside of formal institutions. This work flexibility offers advantages in terms of time and location, but also creates challenges in financial reporting, income uncertainty, and fiscal opacity. This phenomenon contributes to the growth of the shadow economy, namely legal economic activity not recorded in the official system. This study aims to examine the dynamics of digital freelance financial reporting and its implications for the national fiscal system. Using a qualitative case study approach, data was obtained through in-depth interviews with freelancers active on global platforms. The results indicate that low financial literacy, negative perceptions of tax institutions, and the absence of digital platform regulations are the main obstacles to integration into the formal economic system. Freelancers tend to adopt informal strategies to manage their finances, including the use of untraceable cross-border payment systems. This study recommends adaptive policies based on fiscal education, digitalization of reporting systems, and incentives for digital actors and platforms. These findings reinforce the urgency of updating fiscal regulations to address the dynamics of the digital economy and create a reporting system that is more inclusive, accountable, and relevant to the needs of gig economy actors in the era of technological globalization.